2004
DOI: 10.1016/j.jvs.2004.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Mesenteric artery disease in the elderly

Abstract: This investigation provides the first population-based estimate of the prevalence of MAS among independent elderly Americans. MAS existed in 17.5% of the study cohort. The majority had isolated celiac disease. SMA stenosis and celiac artery occlusion demonstrated a significant and independent association with weight loss and concurrent renal artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(83 citation statements)
references
References 17 publications
2
75
0
6
Order By: Relevance
“…In a retrospective study including 980 patients with a mean age of 68 years who underwent angiography for various indications, 8% had significant stenoses of at least one splanchnic artery [9] . In a screening study with duplex ultrasonography in 553 healthy elderly subjects with a mean age of 84 years, stenoses in the celiac artery (CA) or superior mesenteric artery (SMA) were found in 18% [10] . In patients with atherosclerotic disorders of aorta, iliac and femoral vessels the incidence ranged from 25% to 40% [11,12] .…”
Section: Epidemiologymentioning
confidence: 99%
“…In a retrospective study including 980 patients with a mean age of 68 years who underwent angiography for various indications, 8% had significant stenoses of at least one splanchnic artery [9] . In a screening study with duplex ultrasonography in 553 healthy elderly subjects with a mean age of 84 years, stenoses in the celiac artery (CA) or superior mesenteric artery (SMA) were found in 18% [10] . In patients with atherosclerotic disorders of aorta, iliac and femoral vessels the incidence ranged from 25% to 40% [11,12] .…”
Section: Epidemiologymentioning
confidence: 99%
“…However, Hansen et al reported that 12.8% of patients with SMA stenosis had concomitant renal artery stenosis. 8) The American College of Cardiology/American Heart Association 2005 practice guidelines recommended that revascularization of asymptomatic intestinal arterial obstructions may be considered for patients undergoing aortic/renal artery surgery for other indications (Class IIb). 9) Because one-staged revascularization surgery of both renal artery and SMA is less invasive and more beneficial than two-staged surgery in a low-risk patient, we performed SMA bypass surgery simultaneously with AAA repair.…”
Section: Discussionmentioning
confidence: 99%
“…Other causes of CMI include aortic dissection, fibromuscular dysplasia, vasculitides and median arcuate ligament syndrome. Atherosclerotic disease of the mesenteric arteries is estimated to occur in 17% of patients over the age 65 years (Hansen et al, 2004). Despite its prevalence, the majority of these patients are asymptomatic as a result of the extensive collateral circulation between the celiac trunk, superior mesenteric artery (SMA) and inferior mesenteric artery (IMA).…”
Section: Chronic Mesenteric Ischaemiamentioning
confidence: 99%